PENGARUH PENGGUNAAN SMARTPHONE TERHADAP HASIL BELAJAR SISWA SD NEGERI 106162 KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Harahap, Fatma Dewani (Penerbit Widina, Widina Media Utama, 2024)
The use of smartphones in the current era of globalization has become a necessity in the community, because of the availability of feature features that facilitate daily human work, one of which is used by students because it can be a source of lessons for students and can make it easier for students to do assignments from school. From this, the problem discussed in this article is how the use of smartphones and the proper use of smartphones affect the learning outcomes of students in grade V of SD Negeri 106162 Percut Sei Tuan District, Deli Serdang Regency. This research aims to determine the effect of smartphone use on the learning outcomes of fifth grade students at SD NEGERI 106162, Percut Sei Tuan District, Deli Serdang Regency. This research is quantitative research with inferential statistical analysis of product moment correlation coefficients. The population in this study were all students of SD NEGERI 106162, Percut Sei Tuan District, Deli Serdang Regency, the sample was taken using a purposive sampling technique of 24 people. Data was collected through questionnaire and documentation techniques. Based on the results of data analysis, the author found that the